Perbandingan Kinerja Algoritma Linear Search dan Binary Search dalam Pencarian Data - Revaliana Indriyani Surachman; Fidi Supriadi; Asep Saeppani; Fathoni Mahardika (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
Data searching is a fundamental aspect of computer science that affects application performance. This study aims to analyze and compare the efficiency of two basic searching algorithms, namely Linear Search and Binary Search. The research method was conducted by testing both algorithms using datasets with a varying number of elements to measure execution time and algorithm complexity. The results showed that Linear Search is more efficient for small or unsorted data, while Binary Search shows much superior performance on large sorted datasets with a time complexity of O(log n). The conclusion of this study provides guidance in choosing the right searching algorithm based on data characteristics and system requirements.